A review on the quality of data inputs in life cycle cost analysis of rigid pavement maintenance in Malaysia - Ahmad Jasmi, Siti Zulaiha; Ayob, Mohd Fairullazi; Abdul Rashid, Khairuddin (PIBEC Secretariat, 2017)
The implementation of Life Cycle Cost (LCC) analysis is crucial in the cost estimation of rigid pavement type due to the high cost for constructing and maintaining the roads and highways in Malaysia. LCC analysis are being used as a decision support tool when selecting pavement type, which also used to evaluate maintenance strategies for the pavement type. Roads in Malaysia can be divided into two types, i.e. rigid pavement and flexible pavement. In this paper, the study will be focusing on the rigid pavement maintenance since there is very limited number of new construction of rigid pavement in Malaysia. The outcome of the initial study shows that, most of the road construction industry key players are aware that LCC should be practiced and applied in the rigid pavement construction and maintenance. However, one of the major difficulties of implementing the LCC analysis of rigid pavement maintenance is lack of updated and reliable data inputs. Most of the scholars and estimators are mainly focused on the LCC conversion but very limited in emphasizing the quality of data inputs (i.e. availability, accessibility, currency and reliability of data inputs) for producing reliable LCC outputs. The objective of this paper is to review the quality of data inputs of LCC analysis for cost estimation of rigid pavement maintenance. The findings provide current information on the state of quality of data inputs of LCC analysis of rigid pavement maintenance.